ANALISIS POTENSI WISATA RELIGI DAN BUDAYA DI KOTA JAMBI - Wahyu Alkautsar; Nurida Isnaeni; Paulina Lubis (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research focuses on the potential for religious and cultural tourism in the city of Jambi. The aim of this research is to find out the potential and obstacles that occur in tourist destinations and to find out the strategies used to develop these tourist destinations. The method used in this research is a qualitative descriptive method with the Miles and Huberman Model which is then analyzed using SWOT analysis. The research results show that the development of religious and cultural tourism in Jambi City is still not well realized due to the lack of government role and public awareness about tourism, but on the other hand, Jambi City has potential Islamic history and culture. The strategy used can optimize the tourism potential of Jambi City.